ASME 2007 Rail Transportation Division Fall Technical Conference 2007
DOI: 10.1115/rtdf2007-46010
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Full-Scale Tank Car Shell Impact Tests

Abstract: This paper describes analyses of a railroad tank car impacted at its side by a ram car with a rigid punch. This generalized collision, referred to as a shell impact, is examined using nonlinear (i.e., elastic-plastic) finite element analysis (FEA) and three-dimensional (3-D) collision dynamics modeling. Moreover, the analysis results are compared to full-scale test data to validate the models. Commercial software packages are used to carry out the nonlinear FEA (ABAQUS and LS-DYNA) and the 3-D collision dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…Material failure models that account for the influence of stress state on the propensity for fracture [6] have been incorporated into the ABAQUS model. These material failure models have recently been shown to provide excellent agreement to the results from a series of tank car dynamic impact/puncture tests [7]. In addition, material tests are being planned so that the failure models can be calibrated.…”
Section: Discussionmentioning
confidence: 94%
“…Material failure models that account for the influence of stress state on the propensity for fracture [6] have been incorporated into the ABAQUS model. These material failure models have recently been shown to provide excellent agreement to the results from a series of tank car dynamic impact/puncture tests [7]. In addition, material tests are being planned so that the failure models can be calibrated.…”
Section: Discussionmentioning
confidence: 94%
“…The Eulerian formulation is implemented using LS-DYNA. Previous research on tank car shell impacts [6,7] indicated that the Eulerian mesh provided a more accurate representation of fluid-structure interaction than the Lagrangian mesh when compared to test data.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…In current tank car construction, the commodity tank is nominally made with normalized TC-128B steel. The properties listed in the table for TC-128B correspond to tensile measurements performed on tank car that punctured in a full-scale shell impact test [6]. Outer jackets are typically made with A1011 steel.…”
Section: Finite Element Analysismentioning
confidence: 99%
See 2 more Smart Citations